The Impact of Developmental Language Disorder (DLD) onStudents’ Socialization: A Gender Based Study (Journal of Asian Development Studies, 2024)
This study is conducted to examine the effect of Developmental Language Disorder (DLD) on students’ socialization with reference to their gender. This study emphasizes the importance of understanding the differences in the lived experiences of male and female students with DLD, and how the analysis can shed light on their social worldview. Using a quantitative approach and a questionnaire, the study investigated two groups of 20 male and 20 female students with developmental language disorders from two schools for children with special education needs in Gujrat. All participants were chosen through purposive sampling. The analysis of the coded data was conducted using SPSS software, version 16, to reveal statistical insights into the socialization of the students and their gender. It was found that overall, the children with DLD showed low levels of socialization, however, disorder may manifest in different ways in males and females. Interestingly, those with milder forms of the disorder display stronger social abilities in comparison with those with higher severity levels of the condition. DLD can create unique challenges for social interaction, depending on the severity and type of the disorder. Moreover, in boys and girls with DLD there might be differences in social interactions. The study reveals that DLD is far more prevalent in girls than in boys indicate that more girls are likely to be diagnosed with the disorder and their social interactions fall within the low range. Furthermore, the severity of DLD seems to be inversely related to social competence, with milder cases exhibiting better socialization skills. This research is very important since it explores the effects of Developmental Language Disorder (DLD) on the social lives of male and female learners. Thus, in analyzing gender differences in the experience of DLD, the study contributes to coaching potential interventions about how DLD appears in specific social contexts. The results highlight the need to estimate the degree of difference in severity and its connection with social competence that is helpful for the further education of children with DLD. Finally, this research adds to the development of an effective strategy in meeting the needs of students with Developmental Language Disorder.